Hoary fox habitat selection opens livestock grazing management opportunities to combine cattle production and carnivore conservation - FLAVIA FERNANDA WEBER DE SOUZA (2021)
Pasture expansion raises the challenge of improving livestock production while conserving wildlife. Livestock Grazing Management (LGM) is usually designed to boost production, but its relationship with wildlife is little known. Sward surface height (SSH) represents the vegetation structure available to cattle and wildlife. Using SSH as a proxy of LGM, we aim to suggest a management that benefits cattle beef production and conservation of a vulnerable mammal, the hoary fox (Lycalopex vetulus). To do this, we evaluated fox habitat selection in pasturelands under different SSHs of cattle beef private farms on Brazilian savanna. We radio-tracked thirty foxes over ten years and applied Resource Selection Functions to estimate their habitat selection under two biological orders (home-range and within home-range) in two habitat scales (coarse- and fine-grained). For coarse-grained habitats, foxes selected pasture over woodland on both biological orders, as expected due to being a species specialized in open areas. For fine-grained habitats within their home ranges, both sexes selected medium SSH during the day, and females selected low SSH at night. Foxes selected maize crops to feed on insects, and medium and low SSHs to forage, rest, and breed. Our results suggest pro-hoary fox management that can be applied on natural habitats already converted to pastures and reconcile farmers and foxes. Pro-hoary fox management includes a LGM with moderate grazing pressure under a rotational system (providing low and medium SSH) and integrating pasture with small maize crops. This pro-hoary fox management can align improved livestock production with hoary fox conservation.